2009
DOI: 10.1186/1742-2094-6-41
|View full text |Cite
|
Sign up to set email alerts
|

ER stress in Alzheimer's disease: a novel neuronal trigger for inflammation and Alzheimer's pathology

Abstract: The endoplasmic reticulum (ER) is involved in several crucial cellular functions, e.g. protein folding and quality control, maintenance of Ca2+ balance, and cholesterol synthesis. Many genetic and environmental insults can disturb the function of ER and induce ER stress. ER contains three branches of stress sensors, i.e. IRE1, PERK and ATF6 transducers, which recognize the misfolding of proteins in ER and activate a complex signaling network to generate the unfolded protein response (UPR). Alzheimer's disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
214
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(221 citation statements)
references
References 170 publications
(258 reference statements)
5
214
1
1
Order By: Relevance
“…It remains to be clarified whether phosphorylation induced tau LLPS occurs as cause or result of tau mislocalization into the somato‐dendritic compartment of neurons. (iii) The intraneuronal accumulation of tau droplets and aggregated tau in the cell body (e.g., in NFTs) causes not only long‐term toxicity through ER stress and UPR (Salminen et al , 2009), but it also depletes tau from the soluble pool that is essential to maintain microtubule stability. Tau droplets could also have other direct pathological consequences, for example, through aberrant interaction with cellular organelles or “absorption” of RNA molecules, which would impact protein expression and homeostasis of the neuron.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be clarified whether phosphorylation induced tau LLPS occurs as cause or result of tau mislocalization into the somato‐dendritic compartment of neurons. (iii) The intraneuronal accumulation of tau droplets and aggregated tau in the cell body (e.g., in NFTs) causes not only long‐term toxicity through ER stress and UPR (Salminen et al , 2009), but it also depletes tau from the soluble pool that is essential to maintain microtubule stability. Tau droplets could also have other direct pathological consequences, for example, through aberrant interaction with cellular organelles or “absorption” of RNA molecules, which would impact protein expression and homeostasis of the neuron.…”
Section: Discussionmentioning
confidence: 99%
“…ER stress is implicated in the development or pathology of AD [15][16][17] . [21] , insulin resistance of adipose tissue [38] , apoptosis of osteoblastic cells [39] , type 2 diabetes mellitus [40] , and hepatic steatosis [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence indicates that endoplasmic reticulum (ER) stress plays a pivotal role in the development or pathology of AD, which is characterized by an abnormal formation of inclusion bodies and aggregation of misfolded proteins [15][16][17] . The ER is a sophisticated luminal network for the synthesis, www.nature.com/aps Wei HJ et al Acta Pharmacologica Sinica npg maturation, folding, and transportation of proteins, which are required for cell survival and normal cellular functions [18,19] .…”
Section: Introductionmentioning
confidence: 99%
“…17 This becomes a self-perpetuating pathological process, with each pathologic component exacerbating the others. [22][23][24][25][26] We have shown that aspirin, ibuprofen, and resveratrol dampen the PSACH chondrocyte pathology, reducing inflammation and/or oxidative stress. 16 This important and novel therapeutic approach interrupts the pathological loop.…”
Section: Introductionmentioning
confidence: 97%